Knowledge Management About Investigative Work That is The Best Practice of The Detective 4.0 Era - Borwornchai, Dithapart (Arts of Management Journal, 2020)
The purposes of this research were to 1) study the state, problems and solutions for investigation in Thailand 2) manage knowledge of investigation in Thailand. Population used in the research were police officers at operational level, investigative work in police stations under the Metropolitan Police Bureau, Provincial Police Region 1 to 9, Immigration Office, Central Police Headquarters and the Narcotics Suppression Bureau. Former experienced detectives and 1,511 FBI officers and Thai police officers who have completed the FBI training program, using mixed methods, quantitative and qualitative methods. 1.The research found that the problem of investigation work in Thailand is at the average level of average ( = 2.80). When considering each aspect, it is found that the aspect that had the most problems at a medium level was the problems of pre-incident investigation. When considering each item found that the problems that are most ranked in 3 levels are at the moderate level, namely 1) studying behavior of criminals during interrogation 2) training exercise, preparation for strength to work in all situations 3) Investigate local information. Sources of potential crime respectively. 2.Knowledge management, investigation are divided into 1) investigation before the accident that investigators must have an ideology, perseverance and adhere to the work principles. They also have to both be physically and mentally stable. 2) Investigation after the incident that give priority to the treatment of crime scenes, proof of work collection of forensic evidence and question systematically according to psychological processes, investigative techniques and the legal system that facilitate police operations. 3) Investigations in the 4.0 era must be also both physically and mentally ready. The evidence is clear, legally that technology could help with the investigation and investigators have to learn and continuously develop all personnel in the department. There is a central agency to support the validation of personal information legally which should integrate collaboration into a network.